Romanticism - Brown, David Blayney (Art & Ideas, 2006)
Romanticism was a way of feeling rather than a style in art. In the period c.1775-1830 - against the background of the French Revolution and the Napoleonic Wars - European artists, poets and composers initiated their own rebellion against the dominant political, religious and social ethos of the day. Their quest was for personal expression and individual liberation and, in the process, the Romantics transformed the idea of art, seeing it as an instrument of social and psychological change.